(untitled) (Global Journal of Management and Business Research, 2014)
Textile Industry plays an important role in Bangladesh economy It captures 40 of total manufacturing and 50 of total employment A huge 78 percent of the country s export earnings come from textiles and apparel according to the latest figures available Bangladesh exports its apparel products worth nearly 5 billion per year to the United States European Union EU Canada and other countries of the world It is the sixth largest apparel supplier to the United States and EU countries The industry employs about 3 million workers of whom 90 are women So people are most valuable asset The early part of the century saw a concern for improved efficiency through careful design of work During the middle part of the century emphasis shifted to the employee s productivity Recent decades have focused on increased concern for the quality of working life total quality management and worker s participation in management These three phases may be termed as welfare development and empowerment So Human Resource Management HRM is the function within an organization that focuses on recruitment of management of and providing direction for the people who work in the organization Human Resource Management can also be performed by line managers Human Resource Management is the organizational function that deals with issues related to people such as compensation hiring performance management organization development safety wellness benefits employee motivation communication administration and training Human Resource Management has come to be recognized as an inherent part of management which is concerned with the human resources of an organization Its objective is the maintenance of better human relations in the organization by the development application and evaluation of policies procedures and programmers relating to human resources to optimize their contribution towards the realization of organizational objectives